Migration, educational policies & practices: Constructing difference in Buenos Aires & in Madrid - Beech, Jason; Bravo-Moreno, Ana (Education Policy Analysis Archives, 2014)
This article compares school experiences of Latin American immigrants in the cities of Buenos Aires and Madrid, by analyzing migration profiles in each city, migration and educational policies, and a series of interviews that were made with teachers and students in state schools that had a high percentage of foreign students. Both Madrid and Buenos Aires City have experienced substantial changes in the profile of migration trajectories. The growth and visibility of ethnic plurality in two cities that saw themselves as having certain cultural and ethnic homogeneity has created tensions in their educational systems. The article shows that in both cities the overall approach to the education of immigrants is based on the notion of assimilation to an imagined mainstream culture. Within this general approach, misrecognition of the specific needs of immigrant students takes place in schools in both cities, although in very different ways in each location.